(3JQJjH hJgPjH (B( (3cJGH(B) (3GdCNHGQ HPcQ GdYdeGA GdCNjGQs - (3eLghds; (3Gdcahj , eMehO Hf SdjeGf GdMfaj GdQhej,J (B990 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf hYdeg GdHjGf hHYO , aEf GdEeGe eMehO Hf SdjeGf GdTgjQ HGdcahi bO LeY cJGHg GdLdjd GdeSei cJGH GdCNHGQ HPcQ GdYdeGA GdCNjGQ , acGf cJGHkG LGeYkG ddefGbH s
(3BNQgG (B:s
(3ef HGH (B" (3ef YQa HGHf adGf (B" (3, ef MQa GdjGA , bhdg (B: (3GHf QMHGf (B: (3eMeO GdOjdei , hYHO GdhgGH Hf CMeO GHf jYjT (B: (3YHO GdQMef GHf eMeO , hhdOg eMeO Hf Ydi GHf GdjeGf (B: (3GSeg eMeO s
(3HgG fXGe GdJYbjH QJHg Ydi MQha GdeYLes
(3JHUQI GdYfhGf (B:s
(3JgPjH hJQJjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B168s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
Keywords: (3GdJGQjNs